Correlation of clinical and neurophysiological findings with health-related quality of life in patients with diabetic polyneuropathy - Vukojević, Zoran; Pekmezović, Tatjana; Nikolić, Ana; Perić, Stojan; Basta, Ivana; Marjanović, Ivan; Lavrnić, Dragana (Vojnosanitetski pregled, 2014)
Background/Aim. Diabetic polyneuropathy is defined as the presence of clinical or subclinical symptoms and/or signs of peripheral nerve damage in patients with diabetes mellitus in the absence of the other causes of peripheral neuropathy. The aim of this study was to assess health-related quality of life (HRQoL) in patients with diabetic polyneuropathy and its correlation with clinical and neurophysiological findings. Methods. This study comprised 60 patients with distal, symmetric, sensorimotor diabetic polyneuropathy and type 2 diabetes mellitus. For evaluation of clinical findings the following scales were used: Medical Research Council strenth score (MRC sum score), Inflammatory Neuropathy Cause and Treatment (INCAT) disability scale (arm disability and leg disability scales), INCAT sensory sum score, Hamilton depression and anxiety rating scales. Nerve conduction study (NCS) was performed on the motor part of the median and peroneal nerves, the sensory part of the median nerve and sural nerve. All the patients completed the Serbian version of the SF-36 questionnaire as a measure of HRQoL. Results. Our results showed mild to moderate QoL impairment in the patients with diabetic polyneuropathy with no difference in physical and mental composite scores (p > 0.05). The age of the patients, mean MRC sum score, arm disability scale score, leg disability scale score and mean INCAT sensory sum score correlated with scores in the SF-36 questionnaire (p < 0.01). The patients with higher scores of anxiety and depression had significantly worse health perception for all QoL domains, for both composite scores and for the total SF-36 score (p < 0.01). Both motor and sensory NCS parameters of the median nerve showed significant correlations with QoL scores (p < 0.05). Conclusion. Our results showed mild to moderate QoL impairment in the patients with diabetic polyneuropathy. HRQoL significantly correlated with the age of the patients, muscle strength, disability, sensory complaints, depressiveness and anxiety of the patients. Electrophysiological examination of median nerve significantly correlated with QoL in the patients with diabetic polyneuropathy.
Keywords: diabetic neuropathies; neurophysiology; quality of life; questionnaires